The Philippine Embroidery Center - Naig, Ann Bernadette R. (College of Architecture, University of the Philippines Diliman, 2019)
Lumban, also known as the Embroidery Capital of the Philippines, encompasses a long history of the craftsmanship. It is most notable as the municipality in Laguna that centers its industry in embroidery. Having a long history of embroidery since the Spanish colonization, the embroidery of Lumban develops with the changing demand of the industry. But keeping up with these demands comes with challenges. The thesis therefore aims to provide a design project proposal that aids in the development of the municipality of Lumban through the embroidery industry. The embroidery facility also aims to serve as a learning, training, research and advancement center to be a means for the growth of the craftsmanship.